TINGKAT PENGETAHUAN TENTANG MENOPAUSE DENGAN KUALITAS HIDUP WANITA PERIMENOPAUSE DI DESA SAKTI KECAMATAN NUSA PENIDA - Ariani, Ni Komang Sri; Raswati Teja, Ni Made Ayu Yulia (JURNAL MEDIA KESEHATAN, 2021)
Every complaint experienced by menopausal women can cause decreased quality of life. Quality of life is a unique individual perception of dignity and value in the context of culture and value systems, in which individuals exist and are associated with life goals and individual targets. This situation is a description of satisfaction, a sense of well-being, compared to an ideal state or one that should be achieved and reflected in daily activities. The quality of life for menopausal women decreases because menopausal women are not ready to accept menopause. Objectives: to find out whether there is a relationship between the level of knowledge about menopause and the quality of life of perimenopausal women in Sakti Village, Nusa Penida District. Methods: This research is a descriptive analytic study with a cross sectional approach, a sample of 100 respondents who met the inclusion criteria. Results: Most of the level of knowledge possessed by perimenopausal women in Sakti Nusa Penida Village have a good level of knowledge (54%) about menopause, while the quality of life of perimenopausal women in Sakti Village is good, namely 55%. The results of the cross tabulation of the data show that most of the respondents who have a good level of knowledge, namely 31 (31%) people, have a good quality of life too. Meanwhile, 22 (22%) perimenopausal mothers who had less knowledge had a poor quality of life. Meanwhile, the results of hypothesis testing obtained a sig value of 0.600 (sig> 0.05). This means that there is no significant relationship between the level of knowledge and the quality of life of perimenopausal women in Sakti Village, Nusa Penida District.